Pengendalian Mutu Selai Kecombrang Melalui Perbaikan Pengolahan Pada Koperasi Perempuan Pelestari Hutan (KPPH) di Rejang Lebong - Anis, Ulfah; Intara, Yazid Ismi; Yuwana, Yuwana (Universitas Bengkulu, 2023)
Target community of this activity was forest conservative women who produced various food products including jam, syrup, “dodol” cake, and sticks whose qualities needed to be improved. It was observed that the “kecombrang” jam and syrup brought up different colors for each production run. The unpleasant taste was identified in the dodol cake. The jackfruit stick lacked crunchiness which might be due to improper drying. The objective of this community service activity was a technology transfer consisting of three topics: (1) Quality control in material handling to avoid browning of raw material (2) Quality control of food processing to improve the quality of resulting products, and (3) Introduction of food drying utilizing a YSD-UNIB12 solar dryer. The activity included: meeting coordination and material preparation, counseling, and interactive dialogue. The result indicated that 70% mastered the delivery topics and 30% understood some parts of them. Participants were very enthusiastic in participating in the counseling conducted by the team.